Phenotypic and Genotypic Detection of Metallo-Beta-Lactamases in Carbapenem Resistant Acinetobacter baumannii - Zahra Moulana; Arefeh Babazadeh; Zohreh Eslamdost; Mehran Shokri; Soheil Ebrahimpour (Babol University of Medical Sciences, 2020)
Background: Carbapenem resistance in Acinetobacter baumannii has become a major concern for treating physicians. The aim of this study was to investigate the prevalence of metallo β-lactamase (MBL) genes (bla VIM , and blaIMP) among isolated multidrug-resistant A. baumannii . Methods: Fifty non-repetitive carbapenem-resistant A. baumannii isolates were collected. Antibiotic susceptibility was performed by disk diffusion method. MICs were determined by E test method. The resistant strains were tested for the production of carbapenemases by the Modified Hodge Test (MHT) followed by EDTA-disk synergy test was performed for metallo-β-lactamases (MBL) phenotypic detection. Detection of bla VIM , and blaIMP was performed by PCR followed by sequencing. Results: All isolates had a multidrug resistant profile, and were all resistant to all antibiotics including the carbapenems but remained susceptible to colistin. Among these isolates, Carbapenemase production was confirmed by the Modified Hodge test for 42 (84%) isolates. Phenotypic method showed the production of MBL in 15 (30%) isolates. PCR techniques revealed that out of 50 isolates, 13 (26%) were positive for blaVIM and all were negative for blaIMP. Conclusion: Our study concludes that the high prevalence of carbapenem resistant Acinetobacter species with MBL production is one of the main concerns in our country and this situation needs strict infection control measures.